Medium-carbon medium-manganese high-wear-resistance steel with spheroidized ghost pearlite structure and preparation method of medium-carbon medium-manganese high-wear-resistance steel

The preparation of medium-carbon medium-manganese high wear-resistant steel with spherical ghost pearlite tissue through multi-stage treatment method, solving the limitations of existing wear-resistant steels in terms of strength, hardness and wear resistance, and achieving high strain hardening and wear resistance Performance improvement.

CN119464948APending Publication Date: 2025-02-18SOUTHEAST UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411651726.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing wear-resistant steels have limitations in strength, hardness and wear resistance, and it is difficult to meet the needs of high strength and high wear resistance at the same time.

Method used

The medium-carbon medium-manganese high wear-resistant steel with spherical ghost pearlite tissue was prepared by multi-stage treatment method. The stable treatment of layered full pearlite, pearlite spherification, pearlite alienation and spherical ghost pearlite tissue was improved. Residual austenite content and mechanical stability of steel.

Benefits of technology

High strain hardening performance is achieved, significantly improving the wear resistance of the material, shortening the heat treatment time and improving production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119464948A_ABST
    Figure CN119464948A_ABST
Patent Text Reader

Abstract

The invention discloses medium-carbon medium-manganese high-wear-resistance steel with a spheroidized ghost pearlite structure and a preparation method of the medium-carbon medium-manganese high-wear-resistance steel. The medium-carbon medium-manganese high-wear-resistance steel comprises the following chemical elements in percentage by mass: 0.3-0.5% of C, 4-7% of Mn and the balance of Fe and other inevitable impurities. The matrix is martensite, retained austenite is dispersed on the martensite matrix, and the volume fraction of the retained austenite is 20-45%. According to the method, a spheroidized ghost pearlite structure combining spherical retained austenite and martensite is obtained in the medium-carbon medium-manganese steel mainly through multi-stage treatment, and the spheroidized ghost pearlite structure has the ultra-fine grain size and the high retained austenite volume fraction; the special structure enables the medium-carbon medium-manganese steel to have high hardness and high wear resistance. The volume fraction and stability of the retained austenite are improved by regulating the austenite in the pearlite to be spherical, martensite is used as a matrix, excellent strength and plasticity and wear resistance are achieved, and the heat treatment efficiency is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a medium-carbon medium-manganese high wear-resistant steel with a spheroidized ghost pearlite structure and a preparation method thereof, belonging to the technical field of wear-resistant material processing. Background Art

[0002] With the development of industrialization, the mining and transportation industries have put forward higher requirements on the performance of wear-resistant materials. The materials must have high initial hardness and be able to achieve strain hardening through the phase transformation induced plasticity (TRIP) effect during the wear process to improve wear resistance. Therefore, developing new wear-resistant steel materials, optimizing microstructures, and improving their strength and wear resistance can significantly extend equipment life, reduce downtime, and thus improve economic benefits.

[0003] Traditional wear-resistant steels (such as Hadfield steel and martensitic steel) have certain limitations in strength, hardness and wear resistance, and it is difficult to cope with the dual requirements of high strength and wear resistance in different application scenarios. Hadfield steel has a high strain hardening ability, but its hardening effect is limited under medium and low impact or low load conditions, which easily leads to premature wear, limiting its applicability in these environments. On the other hand, although martensitic steel has a high initial hardness and wear resistance, its toughness is poor, and it is difficult to withstand the use requirements under high impact loads. It is prone to brittle fracture or early failure, increasing maintenance and replacement costs. Medium manganese wear-resistant steel shows advantages in these aspects. On the one hand, it can improve the strain hardening ability by increasing the volume fraction of retained austenite, and maintain good mechanical stability, which is suitable for a wider range of application loads. On the other hand, the relatively low manganese content in medium manganese steel is not only more economically attractive, but also makes medium and low manganese components more suitable for welding, thereby further improving the practicality and cost-effectiveness of medium manganese wear-resistant steel. In addition, expanding the application of third-generation advanced high-strength steel in the wear-resistant field is of great significance for improving the comprehensive performance of materials and expanding their application scenarios. It can provide more optimized solutions for fields with high strength and high wear resistance requirements. Summary of the invention

[0004] Purpose of the invention: The first purpose of the present invention is to provide a medium carbon medium manganese high wear resistant steel with spheroidized ghost pearlite structure. The second purpose of the present invention is to provide a preparation method of the medium carbon medium manganese high wear resistant steel with spheroidized ghost pearlite structure.

[0005] Technical solution: The present invention discloses a medium-carbon, medium-manganese high wear-resistant steel with a spheroidized ghost pearlite structure, comprising the following chemical elements in percentage by mass: C: 0.3-0.5%, Mn: 4-7%, and the remainder being Fe and other inevitable impurities; its matrix is ​​martensite, and residual austenite is dispersed in the martensite matrix, and the volume fraction of the residual austenite is 20-45%.

[0006] Furthermore, the grain size of the medium carbon, medium manganese and high wear-resistant steel is less than 150nm.

[0007] Furthermore, the hardness of the medium carbon and medium manganese high wear-resistant steel is greater than 600 HV, and the wear rate is less than 2×10 -5 mm 3 / (N*m).

[0008] The method for preparing the medium-carbon medium-manganese high wear-resistant steel with spheroidized ghost pearlite structure of the present invention comprises the following steps:

[0009] (1) Lamellar full pearlite formation: The hot-rolled steel sheet of medium carbon and medium manganese steel is heated to the austenite region, heat-insulated, furnace-cooled to the pearlite region, heat-insulated, and air-cooled to obtain a steel sheet with a lamellar full pearlite structure;

[0010] (2) pearlite spheroidization: cold rolling the steel plate having a layered full pearlite structure obtained in step (1), then heating the cold rolled steel plate to a pearlite region, and heat-insulating the steel plate to achieve pearlite spheroidization, thereby obtaining a steel plate having a spheroidized pearlite structure;

[0011] (3) pearlite alienation: the steel plate having a spheroidized pearlite structure obtained in step (2) is rapidly heated from room temperature to an austenite region, subjected to heat preservation treatment, and rapidly cooled from the austenite region to room temperature to obtain a steel plate having a spheroidized ghost pearlite structure;

[0012] (4) Spheroidized ghost pearlite structure stabilization treatment: The steel plate having the spheroidized ghost pearlite structure obtained in step (3) is subjected to low temperature tempering treatment.

[0013] Furthermore, in step (1), the temperature of the austenite zone is 720-900°C, the heat preservation treatment is 10-60 minutes, and the rate of cooling with the furnace is less than 1°C / s.

[0014] Furthermore, in step (1), the holding temperature of the pearlite region is 500-600° C., and the holding treatment is performed for 24-96 hours.

[0015] Furthermore, in step (2), the cold rolling reduction ratio is greater than 70%, the pearlite region holding temperature is 500-600° C., and the holding treatment is performed for 12-36 hours.

[0016] Furthermore, in step (3), the holding temperature of the austenite zone is 730-820° C., and the holding treatment is performed for 10-120 seconds.

[0017] Furthermore, in step (3), the heating rate is above 100°C / s, and the cooling rate is above 10°C / s.

[0018] Furthermore, in step (4), the steel plate having the spheroidized ghost pearlite structure is placed in an oil bath furnace at a tempering temperature of 200 to 250° C. for a holding time of 0.5 to 2 h for tempering, or is placed in a salt bath furnace at 250 to 400° C. for a holding time of 0.5 to 1 h for tempering.

[0019] The medium-carbon medium-manganese high wear-resistant steel with spheroidized ghost pearlite structure of the present invention obtains the final structure with high residual austenite content through multi-stage treatment, improves the effect of plastic induced phase transformation of the steel with the structure in the wear resistance process, realizes high strain hardening performance, and thus improves the wear resistance of the material. Specifically, the steel is heated to the austenite region and kept warm after hot rolling, then cooled to the pearlite region and kept warm with the furnace, and then air-cooled to obtain a layered full pearlite structure. This step causes the Mn element to segregate into cementite during the pearlite transformation process. (2) The steel plate with the layered full pearlite structure is cold rolled, then heated to the pearlite region and kept warm, and then quenched to obtain a spheroidized pearlite structure. This step regulates the cementite constituting the pearlite to be spherical or quasi-spherical. (3) The steel plate with the spheroidized pearlite structure is rapidly heated from room temperature to the austenite region, and the difference in diffusion rates between the C element and the Mn element during the austenite phase transformation is utilized to retain the Mn element in the original cementite region. During the reverse phase transformation of austenite, the Mn element has only a single body diffusion channel in the spherical cementite region. Compared with the multiple diffusion channel modes of the grain boundary / phase boundary diffusion channel and the body diffusion channel of the lamellar pearlite, the Mn element content retained in the original cementite region is further increased. The austenite structure of the Mn-rich and Mn-poor regions is formed by rapid cooling, wherein the high Mn content in the Mn-rich region significantly improves the stability of the austenite, which is retained at room temperature to become spherical retained austenite, while the Mn-poor region is transformed into martensite. The spheroidized pearlite structure combines the high strength of martensite and the high plasticity of retained austenite, achieving a simultaneous improvement in strength and plasticity, and significantly improving the wear resistance through plastic-induced phase transformation during the wear resistance process.

[0020] (4) The steel plate with spheroidized ghost pearlite structure is tempered so that the martensite matrix of the spheroidized ghost pearlite structure is transformed into tempered martensite, further improving the toughness.

[0021] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:

[0022] The medium-carbon medium-manganese high wear-resistant steel with spheroidized ghost pearlite structure of the present invention is different from the traditional medium-low carbon medium-manganese steel. The present invention utilizes the characteristic that the diffusion channel of the Mn element in the spherical cementite region has only a single body diffusion channel, and increases the content of the Mn element retained in the cementite precursor region, thereby increasing the content and mechanical stability of the final retained austenite, and improving the shape of the retained austenite. The time of conventional heat treatment is shortened, the production efficiency is improved, and the strength and plasticity of the material are positively improved.

[0023] The invention mainly obtains a spheroidized ghost pearlite structure of spherical retained austenite and martensite in a medium carbon medium manganese steel through multi-stage treatment, wherein the matrix is ​​martensite, the retained austenite is dispersed on the martensite matrix, and has an ultrafine grain size (average grain size is less than 150nm) and a high retained austenite volume fraction (volume fraction can reach 20% to 45%); the special structure enables the medium carbon medium manganese steel to have a high hardness greater than 600HV and a wear rate less than 2.0×10 -5 mm 3 / (N*m) high wear resistance. The present invention improves the volume fraction and stability of retained austenite by adjusting the austenite in the pearlite-like body to be spherical, and uses martensite as the matrix to achieve excellent strength, plasticity and wear resistance, and also greatly improves the heat treatment efficiency. The technical problems of long annealing time, low volume fraction of retained austenite and poor mechanical stability of medium-carbon and medium-manganese steel in the prior art are solved, especially by controlling the shape of the pearlite-like body, while improving production efficiency, the wear resistance of the material is further optimized. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a process flow chart of the preparation of medium carbon medium manganese high wear-resistant steel with spheroidized ghost pearlite structure of the present invention

[0025] Figure 2 is a scanning electron microscope microstructure image of a medium carbon medium manganese high wear resistant steel having a spheroidized ghost pearlite structure prepared in Example 1;

[0026] Figure 3 is a coaxial transmission Kikuchi diffraction (TKD) phase map of the medium-carbon medium-manganese high wear-resistant steel with spheroidized ghost pearlite structure prepared in Example 1;

[0027] Figure 4 It is a high-angle annular dark field scanning transmission electron microscope (HADDF-STEM) microstructure diagram of the medium-carbon medium-manganese high wear-resistant steel with spheroidized ghost pearlite structure prepared in Example 1 and a composition distribution diagram of manganese element measured inside the retained austenite grains;

[0028] Figure 5This is a graph showing the hardness test and wear rate test results of the medium-carbon, medium-manganese high wear-resistant steel 1 with spheroidized ghost pearlite structure prepared in Example 1. DETAILED DESCRIPTION

[0029] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.

[0030] Example 1

[0031] (1) Steel with a specific composition of Fe-0.4C-5.13Mn (Wt%, i.e., 0.4Wt%C, 5.13Wt%Mn, and the balance being Fe and other inevitable impurities) was melted in a vacuum induction furnace to form a 60mm thick ingot, which was then subjected to a homogenization treatment at 1150°C for 24 hours, then subjected to a 1200°C for 1 hour, forged to 20mm, and finished at 1000°C, followed by air cooling to room temperature. The hot-rolled steel plate was subjected to the following treatments:

[0032] (2) Pearlite transformation treatment: Samples were taken from the middle of the hot-rolled plate and austenitized at 850°C in a tubular furnace filled with industrial argon atmosphere. After holding for 10 min, the sample was cooled to 550°C (the furnace cooling rate was 0.17°C / s), kept for 72 h, and air-cooled to room temperature to obtain a steel plate with a layered full pearlite structure.

[0033] (3) Pearlite spheroidization treatment: The steel plate with a lamellar full pearlite structure was cold rolled with a cold rolling reduction ratio of 70%, and then the sample was kept at 550°C for 24 hours in a tubular furnace filled with industrial argon atmosphere, and then air-cooled to room temperature to obtain a steel plate with a spheroidized pearlite structure;

[0034] (4) Spheroidized pearlite alienation treatment: The steel plate with spheroidized pearlite structure is placed in a salt bath furnace at 800°C (heating rate of 100°C / s), kept warm for 10s, and air-cooled to room temperature (cooling rate of 10°C / s) to obtain a steel plate with spheroidized ghost pearlite structure;

[0035] (5) Spheroidized ghost pearlite tempering treatment: The steel plate with spheroidized ghost pearlite structure is placed in a 200°C oil bath furnace for 30 minutes and air-cooled to room temperature to obtain a medium-carbon, medium-manganese, high-wear-resistant steel with spheroidized ghost pearlite structure. The specific preparation process is as follows: Figure 1 shown.

[0036] The medium carbon medium manganese high wear-resistant steel with spheroidized ghost pearlite structure prepared in this embodiment was subjected to scanning electron microscope analysis using a Guoyi Quantum SEM 4000 scanning electron microscope (working voltage was 15 kV). The results are as follows: Figure 2 shown. Figure 2is a scanning electron microscope microstructure image of a medium carbon medium manganese high wear resistant steel having a spheroidized ghost pearlite structure prepared in Example 1. Figure 2 It can be seen that the spheroidized ghost pearlite structure consists of tempered martensite matrix and spherical austenite (corrosion pits).

[0037] The coaxial transmission Kikuchi diffraction phase composition analysis of the medium carbon medium manganese high wear-resistant steel with spheroidized ghost pearlite structure prepared in this example is shown in the following results. Figure 3 shown. Figure 3 is a coaxial transmission Kikuchi diffraction (TKD) phase map of the medium carbon medium manganese high wear-resistant steel with spheroidized ghost pearlite structure prepared in Example 1, Figure 3 visible, Figure 3 Medium grey is tempered martensite, light grey is austenite, and dark grey is cementite.

[0038] The medium carbon medium manganese high wear-resistant steel with spheroidized ghost pearlite structure prepared in this embodiment was analyzed by transmission electron microscope. The results are as follows: Figure 4 shown. Figure 4 The high-angle annular dark field scanning transmission electron microscope (HADDF-STEM) microstructure diagram of the medium-carbon medium-manganese high wear-resistant steel with spheroidized ghost pearlite structure prepared in Example 1 and the composition distribution diagram of the manganese element measured inside the retained austenite grains are shown in FIG. Figure 4 visible, Figure 4 The medium white is spheroidized austenite, and the line scanning results show that the Mn content of austenite is as high as 18%.

[0039] The hardness and wear rate of the medium carbon medium manganese high wear-resistant steel with spheroidized ghost pearlite structure prepared in this embodiment were tested. The results are as follows: Figure 5 shown. Figure 5 1 is a graph showing the hardness test and wear rate test results of the medium-carbon medium-manganese high wear-resistant steel 1 having a spheroidized ghost pearlite structure prepared in Example 1. Figure 5 It can be seen that the hardness of the medium-carbon medium-manganese high wear-resistant steel with spheroidized ghost pearlite structure prepared in this embodiment is 608.43HV, and the wear rate is 1.938×10 -5 mm 3 / (N*m).

[0040] The steel sample treated by the method of the present invention has a microstructure of retained austenite + tempered martensite, fine spherical retained austenite is evenly distributed in the tempered martensite matrix, the volume fraction of retained austenite is 27.6%, and the average grain size is 128nm, achieving high hardness and high wear resistance.

[0041] Example 2

[0042] The preparation process is the same as that of Example 1, except that the carbon element composition in the initial steel is different, and is modified to Fe-0.2C-5.13Mn (Wt%), Fe-0.3C-5.13Mn (Wt%), Fe-0.5C-5.13Mn (Wt%) and Fe-0.6C-5.13Mn (Wt%), respectively, as follows:

[0043] (1) Steels with specific compositions of Fe-0.2C-5.13Mn (Wt%), Fe-0.3C-5.13Mn (Wt%), Fe-0.5C-5.13Mn (Wt%) and Fe-0.6C-5.13Mn (Wt%) were smelted in a vacuum induction furnace to form ingots with a thickness of 60 mm. The ingots were homogenized by keeping them at 1150°C for 24 h, then kept at 1200°C for 1 h, forged to 20 mm, and finished rolled at 1000°C, and then air-cooled to room temperature. The hot-rolled steel plates were treated as follows:

[0044] (2) Pearlite transformation treatment: Samples were taken from the middle of the hot-rolled plate and austenitized at 850 °C in a tubular furnace filled with industrial argon atmosphere. After holding the temperature for 10 min, the sample was cooled to 550 °C (the furnace cooling rate was 0.17 °C / s), held for 72 h, and air-cooled to room temperature to obtain a steel plate with a layered full pearlite structure.

[0045] (3) Pearlite spheroidization treatment: The steel plate with a lamellar full pearlite structure was cold rolled with a cold rolling reduction ratio of 70%, and then the sample was kept at 550°C for 24 hours in a tubular furnace filled with industrial argon atmosphere, and air-cooled to room temperature to obtain a steel plate with a spheroidized pearlite structure;

[0046] (4) Spheroidized pearlite alienation treatment: The steel plate with spheroidized pearlite structure is placed in a salt bath furnace at 800°C (heating rate of 100°C / s), kept warm for 10s, and air-cooled to room temperature (cooling rate of 10°C / s) to obtain a steel plate with spheroidized ghost pearlite structure;

[0047] (5) Spheroidized ghost pearlite tempering treatment: The steel plate with spheroidized ghost pearlite structure is placed in a 200°C oil bath furnace for 30 min and air-cooled to room temperature, i.e., Group 4 medium carbon and medium manganese high wear-resistant steel.

[0048] The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by the test embodiment with the specific composition of Fe-0.3C-5.13Mn (Wt%) is uniformly distributed spherical retained austenite + tempered martensite, with spheroidized ghost pearlite structure, the volume fraction of retained austenite is 28.7%, the average grain size is 121nm, the hardness is 605.36HV, and the wear resistance is 1.921×10 -5 mm 3 / (N*m). The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared with the specific composition of Fe-0.5C-5.13Mn (Wt%) is uniformly distributed spherical retained austenite + tempered martensite, with spheroidized ghost pearlite structure, the volume fraction of retained austenite is 27.1%, the average grain size is 126nm, the hardness is 603.52HV, and the wear resistance is 1.965×10 -5 mm 3 / (N*m). The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared with the specific composition of Fe-0.2C-5.13Mn (Wt%) is tempered martensite + a small amount of retained austenite, accompanied by a small amount of cementite. The volume fraction of retained austenite is 17.8%, the average grain size is 145nm, the hardness is 575.25HV, and the wear resistance is 2.428×10 -5 mm3 / (N·m). The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared with the specific composition of Fe-0.6C-5.13Mn (Wt%) is tempered martensite + high volume fraction spherical retained austenite, the volume fraction of retained austenite is 24.0%, the average grain size is 176nm, the hardness is 526.76HV, and the wear resistance is 3.813×10 -5 mm3 / (N·m).

[0049] Example 3

[0050] The preparation process is the same as that of Example 1, except that the manganese element composition in the initial steel is different, and is changed to Fe-0.4C-3Mn (Wt%), Fe-0.4C-4Mn (Wt%), Fe-0.4C-7Mn (Wt%) and Fe-0.4C-8Mn (Wt%), as follows:

[0051] (1) Steels with specific compositions of Fe-0.4C-3Mn (Wt%), Fe-0.4C-4Mn (Wt%), Fe-0.4C-7Mn (Wt%) and Fe-0.4C-8Mn (Wt%) were melted in a vacuum induction furnace to form ingots with a thickness of 60 mm. The ingots were subjected to a homogenization treatment at 1150°C for 24 h, and then forged to 20 mm after being kept at 1200°C for 1 h. The final rolling temperature was 1000°C, and then air-cooled to room temperature. The hot-rolled steel plates were subjected to the following treatments:

[0052] (2) Pearlite transformation treatment: Samples were taken from the middle of the hot-rolled plate and austenitized at 850 °C in a tubular furnace filled with industrial argon atmosphere. After holding the temperature for 10 min, the sample was cooled to 550 °C (the furnace cooling rate was 0.17 °C / s), held for 72 h, and air-cooled to room temperature to obtain a steel plate with a layered full pearlite structure.

[0053] (3) Pearlite spheroidization treatment: The steel plate with a lamellar full pearlite structure was cold rolled with a cold rolling reduction ratio of 70%, and then the sample was kept at 550°C for 24 hours in a tubular furnace filled with industrial argon atmosphere, and air-cooled to room temperature to obtain a steel plate with a spheroidized pearlite structure;

[0054] (4) Spheroidized pearlite alienation treatment: The steel plate with spheroidized pearlite structure is placed in a salt bath furnace at 800°C (heating rate of 100°C / s), kept warm for 10s, and air-cooled to room temperature (cooling rate of 10°C / s) to obtain a steel plate with spheroidized ghost pearlite structure;

[0055] (5) Spheroidized ghost pearlite tempering treatment: The steel plate with spheroidized ghost pearlite structure was placed in a 200°C oil bath furnace for 30 min and air-cooled to room temperature to obtain 4 groups of medium carbon and medium manganese high wear-resistant steels.

[0056] The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by the test embodiment with the specific composition of Fe-0.4C-4Mn (Wt%) is uniformly distributed spherical retained austenite + tempered martensite, with spheroidized ghost pearlite structure, the volume fraction of retained austenite is 28.7%, the average grain size is 133nm, the hardness is 607.21HV, and the wear resistance is 1.912×10 - 5 mm 3 / (N*m). The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared with the specific composition of Fe-0.4C-7Mn (Wt%) is uniformly distributed spherical retained austenite + tempered martensite, with spheroidized ghost pearlite structure, the volume fraction of retained austenite is 31.7%, the average grain size is 137nm, the hardness is 605.18HV, and the wear resistance is 1.936×10 -5 mm 3 / (N*m). The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared with the specific composition of Fe-0.4C-3Mn (Wt%) is tempered martensite + a small amount of retained austenite, accompanied by a martensite block area, the volume fraction of retained austenite is 19.5%, the average grain size is 135nm, the hardness is 580.27HV, and the wear resistance is 2.319×10 -5 mm3 / (N·m). The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared with the specific composition of Fe-0.4C-8Mn (Wt%) is tempered martensite + spherical retained austenite, accompanied by some coarse lath austenite, the volume fraction of retained austenite is 23.5%, the average grain size is 160nm, the hardness is 530.27HV, and the wear resistance is 3.218×10 -5 mm3 / (N·m).

[0057] Example 4

[0058] The composition of each element in the initial steel and the preparation process are the same as in Example 1, except that the austenite zone holding temperatures in the pearlite transformation treatment are different, and are changed to 700°C, 720°C, 900°C and 930°C respectively as follows:

[0059] (1) Steel with a specific composition of Fe-0.4C-5.13Mn (wt%) was melted in a vacuum induction furnace to form a steel ingot with a thickness of 60 mm. The ingot was subjected to a homogenization treatment at 1150°C for 24 hours, then forged to 20 mm after being kept at 1200°C for 1 hour, and the final rolling temperature was 1000°C, followed by air cooling to room temperature. The hot-rolled steel plate was treated as follows:

[0060] (2) Pearlite transformation treatment: Samples were taken from the middle of the hot-rolled plate and austenitized at 700°C, 720°C, 900°C or 930°C in a tubular furnace filled with industrial argon atmosphere. After holding the temperature for 10 min, the samples were cooled to 550°C (the furnace cooling rate was less than 1°C / s), kept for 72 h, and air-cooled to room temperature to obtain a steel plate with a layered full pearlite structure.

[0061] (3) Pearlite spheroidization treatment: The steel plate with a lamellar full pearlite structure was cold rolled with a cold rolling reduction ratio of 70%, and then the sample was kept at 550°C for 24 hours in a tubular furnace filled with industrial argon atmosphere, and air-cooled to room temperature to obtain a steel plate with a spheroidized pearlite structure;

[0062] (4) Spheroidized pearlite alienation treatment: The steel plate with spheroidized pearlite structure is placed in a salt bath furnace at 800°C (heating rate of 100°C / s), kept warm for 10s, and air-cooled to room temperature (cooling rate of 10°C / s) to obtain a steel plate with spheroidized ghost pearlite structure;

[0063] (5) Spheroidized ghost pearlite tempering treatment: The steel plate with spheroidized ghost pearlite structure was placed in a 200°C oil bath furnace for 30 min and air-cooled to room temperature to obtain 4 groups of medium carbon and medium manganese high wear-resistant steels.

[0064] The microstructure of the medium carbon and medium manganese high wear-resistant steel obtained by the pearlite transformation treatment of this embodiment at a holding temperature of 720°C is uniformly distributed spherical retained austenite + tempered martensite, with a spheroidized ghost pearlite structure, a retained austenite volume fraction of 30.5%, an average grain size of 115nm, a hardness of 615.72HV, and a wear resistance of 1.857×10 -5 mm 3 / (N*m). The microstructure of the medium carbon and medium manganese high wear-resistant steel obtained by pearlite transformation treatment with austenite zone holding temperature of 900℃ is uniformly distributed spherical retained austenite + tempered martensite, with spheroidized ghost pearlite structure, the volume fraction of retained austenite is 28.5%, the average grain size is 125nm, the hardness is 609.32HV, and the wear resistance is 1.927×10 -5 mm 3 / (N*m). The microstructure of the medium carbon and medium manganese high wear-resistant steel obtained by pearlite transformation treatment with austenite zone holding temperature of 700℃ is tempered martensite + a small amount of retained austenite, accompanied by some cementite, the volume fraction of retained austenite is 15.8%, the average grain size is 145nm, the hardness is 563.69HV, and the wear resistance is 2.523×10 -5 mm3 / (N·m), and the microstructure of the medium carbon and medium manganese high wear-resistant steel obtained by pearlite transformation treatment with austenite zone holding temperature of 930℃ is tempered martensite + spherical retained austenite, but accompanied by some coarse lath martensite, the volume fraction of retained austenite is 18.2%, the average grain size is 152nm, the hardness is 571.87HV, and the wear resistance is 2.413×10 -5 mm3 / (N·m).

[0065] Example 5

[0066] The composition of each element in the initial steel and the preparation process are the same as in Example 1, except that the holding time in the austenite zone of the pearlite transformation treatment is different, which is changed to 5min, 20min, 60min and 90min respectively as follows:

[0067] (1) Steel with a specific composition of Fe-0.4C-5.13Mn (wt%) was melted in a vacuum induction furnace to form a steel ingot with a thickness of 60 mm. The ingot was subjected to a homogenization treatment at 1150°C for 24 hours, then forged to 20 mm after being kept at 1200°C for 1 hour, and the final rolling temperature was 1000°C, followed by air cooling to room temperature. The hot-rolled steel plate was treated as follows:

[0068] (2) Pearlite transformation treatment: Samples were taken from the middle of the hot-rolled plate and austenitized at 850°C in a tubular furnace filled with industrial argon atmosphere. The samples were kept at this temperature for 5 min, 20 min, 60 min or 90 min, respectively, and then cooled to 550°C (the furnace cooling rate was 0.17°C / s). The samples were kept at this temperature for 72 h and then air-cooled to room temperature to obtain a steel plate with a layered full pearlite structure.

[0069] (3) Pearlite spheroidization treatment: The steel plate with a lamellar full pearlite structure was cold rolled with a cold rolling reduction ratio of 70%, and then the sample was kept at 550°C for 24 hours in a tubular furnace filled with industrial argon atmosphere, and air-cooled to room temperature to obtain a steel plate with a spheroidized pearlite structure;

[0070] (4) Spheroidized pearlite alienation treatment: The steel plate with spheroidized pearlite structure is placed in a salt bath furnace at 800°C (heating rate of 100°C / s), kept warm for 10s, and air-cooled to room temperature (cooling rate of 10°C / s) to obtain a steel plate with spheroidized ghost pearlite structure;

[0071] (5) Spheroidized ghost pearlite tempering treatment: The steel plate with spheroidized ghost pearlite structure was placed in a 200°C oil bath furnace for 30 min and air-cooled to room temperature to obtain 4 groups of medium carbon and medium manganese high wear-resistant steels.

[0072] The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by the pearlite transformation treatment in this embodiment with a holding time of 20 min in the austenite zone is uniformly distributed spherical retained austenite + tempered martensite, with a spheroidized ghost pearlite structure, a retained austenite volume fraction of 30.5%, an average grain size of 135 nm, a hardness of 602.31 HV, and a wear resistance of 1.981×10 -5 mm 3 / (N*m). The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by pearlite transformation treatment with austenite holding time of 60min is uniformly distributed spherical retained austenite + tempered martensite, with spheroidized ghost pearlite structure, the volume fraction of retained austenite is 31.2%, the average grain size is 137nm, the hardness is 605.26HV, and the wear resistance is 1.937×10 -5 mm 3 / (N*m). The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by the pearlite transformation treatment and the holding time of the austenite zone for 5 min is tempered martensite + spherical retained austenite, but the retained austenite is unevenly distributed, the volume fraction of retained austenite is 20.3%, the average grain size is 130nm, the hardness is 592.32HV, and the wear resistance is 2.281×10 -5 mm3 / (N·m). The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by the pearlite transformation treatment and the holding time of the austenite zone for 90min is tempered martensite + spherical retained austenite. However, due to the growth of austenite grains, coarse retained austenite appears in some areas. The volume fraction of retained austenite is 25.1%, the average grain size is 160nm, the hardness is 582.12HV, and the wear resistance is 2.325×10 -5 mm3 / (N·m).

[0073] Example 6

[0074] The composition of each element in the initial steel and the preparation process are the same as in Example 1, except that the cooling rates during the pearlite transformation treatment are different, and are changed to 0.5°C / s and 5°C / s respectively, as follows:

[0075] (1) Steel with a specific composition of Fe-0.4C-5.13Mn (wt%) was melted in a vacuum induction furnace to form a steel ingot with a thickness of 60 mm. The ingot was subjected to a homogenization treatment at 1150°C for 24 hours, then forged to 20 mm after being kept at 1200°C for 1 hour, and the final rolling temperature was 1000°C, followed by air cooling to room temperature. The hot-rolled steel plate was treated as follows:

[0076] (2) Pearlite transformation treatment: Samples were taken from the middle of the hot-rolled plate and austenitized at 850°C in a tubular furnace filled with industrial argon atmosphere. After holding the temperature for 10 min, the sample was cooled to 550°C (the furnace cooling rate was 0.5°C / s or 5°C / s), held for 72 h, and air-cooled to room temperature to obtain a steel plate with a layered full pearlite structure.

[0077] (3) Pearlite spheroidization treatment: The steel plate with a layered full pearlite structure was cold rolled with a cold rolling reduction ratio of 80%, and then the sample was kept at 550°C for 24 hours in a tubular furnace filled with an industrial argon atmosphere and air-cooled to room temperature to obtain a steel plate with a spheroidized pearlite structure;

[0078] (4) Spheroidized pearlite alienation treatment: The steel plate with spheroidized pearlite structure is placed in a salt bath furnace at 800°C (heating rate of 100°C / s), kept warm for 10s, and air-cooled to room temperature (cooling rate of 10°C / s) to obtain a steel plate with spheroidized ghost pearlite structure;

[0079] (5) Spheroidized ghost pearlite tempering treatment: The steel plate with spheroidized ghost pearlite structure was placed in a 200°C oil bath furnace for 30 min and air-cooled to room temperature to obtain two groups of medium carbon and medium manganese high wear-resistant steels.

[0080] The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by the pearlite transformation treatment in this embodiment with a furnace cooling rate of 0.5°C / s is uniformly distributed spherical retained austenite + tempered martensite, with a spheroidized ghost pearlite structure, a retained austenite volume fraction of 25.2%, an average grain size of 121nm, a hardness of 603.58HV, and a wear resistance of 1.981×10 -5 mm 3 / (N*m). The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by pearlite transformation treatment with a furnace cooling rate of 5℃ / s is tempered martensite + spherical retained austenite, but the austenite is unevenly distributed, accompanied by some fine flake cementite, the volume fraction of retained austenite is 25.3%, the average grain size is 141nm, its hardness is 570.45HV, and the wear resistance is 2.214×10 -5 mm3 / (N·m).

[0081] Example 7

[0082] The composition of each element in the initial steel and the preparation process are the same as those in Example 1, except that the holding temperatures of the pearlite region in the pearlite transformation treatment are different, and are changed to 450° C., 500° C., 600° C. and 700° C., respectively, as follows:

[0083] (1) Steel with a specific composition of Fe-0.4C-5.13Mn (wt%) was melted in a vacuum induction furnace to form a steel ingot with a thickness of 60 mm. The ingot was subjected to a homogenization treatment at 1150°C for 24 hours, then forged to 20 mm after being kept at 1200°C for 1 hour, and the final rolling temperature was 1000°C, followed by air cooling to room temperature. The hot-rolled steel plate was treated as follows:

[0084] (2) Pearlite transformation treatment: Samples were taken from the middle of the hot-rolled plate and austenitized at 850°C in a tubular furnace filled with industrial argon atmosphere. After holding the temperature for 10 min, the samples were cooled to 450°C, 500°C, 600°C or 700°C (the furnace cooling rate was 0.17°C / s), respectively, and then kept at this temperature for 72 h. The samples were then air-cooled to room temperature to obtain steel plates with a layered full pearlite structure.

[0085] (3) Pearlite spheroidization treatment: The steel plate with a layered full pearlite structure was cold rolled with a cold rolling reduction ratio of 80%, and then the sample was kept at 550°C for 24 hours in a tubular furnace filled with an industrial argon atmosphere and air-cooled to room temperature to obtain a steel plate with a spheroidized pearlite structure;

[0086] (4) Spheroidized pearlite alienation treatment: The steel plate with spheroidized pearlite structure is placed in a salt bath furnace at 800°C (heating rate of 100°C / s), kept warm for 10s, and air-cooled to room temperature (cooling rate of 10°C / s) to obtain a steel plate with spheroidized ghost pearlite structure;

[0087] (5) Spheroidized ghost pearlite tempering treatment: The steel plate with spheroidized ghost pearlite structure was placed in a 200°C oil bath furnace for 30 min and air-cooled to room temperature to obtain 4 groups of medium carbon and medium manganese high wear-resistant steels.

[0088] The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by the pearlite transformation treatment of this embodiment at a holding temperature of 500°C is uniformly distributed spherical retained austenite + tempered martensite, with a spheroidized ghost pearlite structure, a retained austenite volume fraction of 25.2%, an average grain size of 135nm, a hardness of 604.31HV, and a wear resistance of 1.943×10 -5 mm 3 / (N*m). The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by pearlite transformation treatment with a pearlite zone holding temperature of 600℃ is uniformly distributed spherical retained austenite + tempered martensite, with spheroidized ghost pearlite structure, the volume fraction of retained austenite is 32.2%, the average grain size is 125nm, the hardness is 609.28HV, and the wear resistance is 1.831×10 - 5 mm 3 / (N*m). The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by pearlite transformation treatment at a holding temperature of 450℃ is tempered martensite + spherical retained austenite, but with more cementite precipitation. The volume fraction of retained austenite is 18.7%, the average grain size is 138nm, the hardness is 590.32HV, and the wear resistance is 2.347×10 -5 mm3 / (N·m). The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by pearlite transformation treatment with a pearlite zone holding temperature of 700℃ is tempered martensite + spherical retained austenite. The austenite distribution in some areas is coarse, the volume fraction of retained austenite is 27.6%, the average grain size is 207nm, the hardness is 535.78HV, and the wear resistance is 2.845×0 -5 mm3 / (N·m).

[0089] Example 8

[0090] The composition of each element in the initial steel and the preparation process are the same as those in Example 1, except that the holding time of the pearlite region in the pearlite transformation treatment is different, which is changed to 18h, 24h, 96h and 120h respectively, as follows:

[0091] (1) Steel with a specific composition of Fe-0.4C-5.13Mn (wt%) was melted in a vacuum induction furnace to form a steel ingot with a thickness of 60 mm. The ingot was subjected to a homogenization treatment at 1150°C for 24 hours, then forged to 20 mm after being kept at 1200°C for 1 hour, and the final rolling temperature was 1000°C, followed by air cooling to room temperature. The hot-rolled steel plate was treated as follows:

[0092] (2) Pearlite transformation treatment: Samples were taken from the middle of the hot-rolled plate and austenitized at 850 °C in a tubular furnace filled with industrial argon atmosphere. After being kept at this temperature for 10 min, the sample was cooled to 550 °C (the furnace cooling rate was 0.17 °C / s), kept at this temperature for 18 h, 24 h, 96 h and 120 h respectively, and then air-cooled to room temperature to obtain a steel plate with a layered full pearlite structure.

[0093] (3) Pearlite spheroidization treatment: The steel plate with a layered full pearlite structure was cold rolled with a cold rolling reduction ratio of 80%, and then the sample was kept at 550°C for 24 hours in a tubular furnace filled with an industrial argon atmosphere and air-cooled to room temperature to obtain a steel plate with a spheroidized pearlite structure;

[0094] (4) Spheroidized pearlite alienation treatment: The steel plate with spheroidized pearlite structure is placed in a salt bath furnace at 800°C (heating rate of 100°C / s), kept warm for 10s, and air-cooled to room temperature (cooling rate of 10°C / s) to obtain a steel plate with spheroidized ghost pearlite structure;

[0095] (5) Spheroidized ghost pearlite tempering treatment: The steel plate with spheroidized ghost pearlite structure was placed in a 200°C oil bath furnace for 30 min and air-cooled to room temperature to obtain 4 groups of medium carbon and medium manganese high wear-resistant steels.

[0096] The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by the pearlite transformation treatment of this embodiment with a holding time of 24h in the pearlite zone is uniformly distributed spherical retained austenite + tempered martensite, with a spheroidized ghost pearlite structure, a retained austenite volume fraction of 25.2%, an average grain size of 135nm, a hardness of 604.31HV, and a wear resistance of 1.943×10 -5 mm 3 / (N*m). The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by the pearlite transformation treatment of this embodiment with a holding time of 96h is uniformly distributed spherical retained austenite + tempered martensite, with a spheroidized ghost pearlite structure, a retained austenite volume fraction of 22.8%, an average grain size of 131nm, a hardness of 608.28HV, and a wear resistance of 1.912×10 -5 mm 3 / (N*m). The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by pearlite transformation treatment with a holding time of 18h is tempered martensite + spherical retained austenite, but the retained austenite content is low and unevenly distributed. The volume fraction of retained austenite is 21.8%, the average grain size is 132nm, the hardness is 598.34HV, and the wear resistance is 2.127×10 -5mm3 / (N·m). The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by pearlite transformation treatment with a holding time of 120h is tempered martensite + spherical retained austenite, but the austenite grains are significantly refined and evenly distributed. The volume fraction of retained austenite is 23.4%, the average grain size is 155nm, the hardness is 565.45HV, and the wear resistance is 2.561×10 -5 mm3 / (N·m).

[0097] Example 9

[0098] The composition of each element in the initial steel and the preparation process are the same as in Example 1, except that the cold rolling reduction ratios during the pearlite spheroidization treatment are different, and are changed to 60% and 80% respectively, as follows:

[0099] (1) Steel with a specific composition of Fe-0.4C-5.13Mn (wt%) was melted in a vacuum induction furnace to form a steel ingot with a thickness of 60 mm. The ingot was subjected to a homogenization treatment at 1150°C for 24 hours, then forged to 20 mm after being kept at 1200°C for 1 hour, and the final rolling temperature was 1000°C, followed by air cooling to room temperature. The hot-rolled steel plate was treated as follows:

[0100] (2) Pearlite transformation treatment: Samples were taken from the middle of the hot-rolled plate and austenitized at 850 °C in a tubular furnace filled with industrial argon atmosphere. After holding the temperature for 10 min, the sample was cooled to 550 °C (the furnace cooling rate was 0.17 °C / s), held for 72 h, and air-cooled to room temperature to obtain a steel plate with a layered full pearlite structure.

[0101] (3) Pearlite spheroidization treatment: The steel sheet with lamellar full pearlite structure was cold rolled with a cold rolling reduction ratio of 60% or 80%, and then the sample was kept at 550°C for 24 hours in a tubular furnace filled with industrial argon atmosphere and air-cooled to room temperature to obtain a steel sheet with spheroidized pearlite structure;

[0102] (4) Spheroidized pearlite alienation treatment: The steel plate with spheroidized pearlite structure is placed in a salt bath furnace at 800°C (heating rate of 100°C / s), kept warm for 10s, and air-cooled to room temperature (cooling rate of 10°C / s) to obtain a steel plate with spheroidized ghost pearlite structure;

[0103] (5) Spheroidized ghost pearlite tempering treatment: The steel plate with spheroidized ghost pearlite structure was placed in a 200°C oil bath furnace for 30 min and air-cooled to room temperature to obtain two groups of medium carbon and medium manganese high wear-resistant steels.

[0104] The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by the cold rolling reduction rate of 80% with pearlite spheroidization treatment in this embodiment is uniformly distributed spherical retained austenite + tempered martensite, with a spheroidized ghost pearlite structure, a retained austenite volume fraction of 22.7%, an average grain size of 133nm, a hardness of 606.13HV, and a wear resistance of 1.928×10 - 5 mm 3 / (N*m). The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by the pearlite spheroidization treatment and the cold rolling reduction ratio of 60% is tempered martensite + spherical retained austenite. However, due to insufficient cold rolling, the spheroidization of some areas is incomplete. The volume fraction of retained austenite is 24.6%, the average grain size is 145nm, the hardness is 590.32HV, and the wear resistance is 2.312×10 -5 mm3 / (N·m).

[0105] Example 10

[0106] The composition of each element in the initial steel and the preparation process are the same as those in Example 1, except that the holding temperatures of the pearlite region in the pearlite spheroidization treatment are different, and are changed to 450° C., 500° C., 600° C. and 700° C. respectively as follows:

[0107] (1) Steel with a specific composition of Fe-0.4C-5.13Mn (wt%) was melted in a vacuum induction furnace to form a steel ingot with a thickness of 60 mm. The ingot was subjected to a homogenization treatment at 1150°C for 24 hours, then forged to 20 mm after being kept at 1200°C for 1 hour, and the final rolling temperature was 1000°C, followed by air cooling to room temperature. The hot-rolled steel plate was treated as follows:

[0108] (2) Pearlite transformation treatment: Samples were taken from the middle of the hot-rolled plate and austenitized at 850 °C in a tubular furnace filled with industrial argon atmosphere. After holding the temperature for 10 min, the sample was cooled to 550 °C (the furnace cooling rate was 0.17 °C / s), held for 72 h, and air-cooled to room temperature to obtain a steel plate with a layered full pearlite structure.

[0109] (3) Pearlite spheroidization treatment: The steel sheet with lamellar full pearlite structure was cold rolled with a cold rolling reduction ratio of 70%, and then the sample was kept at 450°C, 500°C, 600°C or 700°C for 24 h in a tubular furnace filled with industrial argon atmosphere, and then air-cooled to room temperature to obtain a steel sheet with spheroidized pearlite structure;

[0110] (4) Spheroidized pearlite alienation treatment: The steel plate with spheroidized pearlite structure is placed in a salt bath furnace at 800°C (heating rate of 100°C / s), kept warm for 10s, and air-cooled to room temperature (cooling rate of 10°C / s) to obtain a steel plate with spheroidized ghost pearlite structure;

[0111] (5) Spheroidized ghost pearlite tempering treatment: The steel plate with spheroidized ghost pearlite structure was placed in a 200°C oil bath furnace for 30 min and air-cooled to room temperature to obtain 4 groups of medium carbon and medium manganese high wear-resistant steels.

[0112] The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by pearlite spheroidization treatment in this embodiment at a holding temperature of 500°C is uniformly distributed spherical retained austenite + tempered martensite, with a spheroidized ghost pearlite structure, a retained austenite volume fraction of 27.3%, an average grain size of 135nm, a hardness of 608.29HV, and a wear resistance of 1.892×10 -5 mm 3 / (N*m). The microstructure of the medium carbon medium manganese high wear-resistant steel prepared by pearlite spheroidization treatment in this embodiment at a holding temperature of 600°C is uniformly distributed spherical retained austenite + tempered martensite, with a spheroidized ghost pearlite structure, a retained austenite volume fraction of 31.2%, an average grain size of 122nm, a hardness of 613.37HV, and a wear resistance of 1.875×10 -5 mm 3 / (N*m). The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by pearlite spheroidization at a pearlite zone holding temperature of 450℃ is tempered martensite + spherical retained austenite. However, due to the low spheroidization temperature, the precipitation of cementite increases, the volume fraction of retained austenite is 22.8%, the average grain size is 148nm, the hardness is 582.47HV, and the wear resistance is 2.365×10 -5 mm3 / (N·m). The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by pearlite spheroidization with a pearlite zone holding temperature of 700℃ is tempered martensite + spherical retained austenite. However, due to the high spheroidization temperature, part of the austenite is recrystallized. The volume fraction of retained austenite is 21.2%, the average grain size is 156nm, the hardness is 575.84HV, and the wear resistance is 2.321×10 -5 mm3 / (N·m).

[0113] Embodiment 11

[0114] The composition of each element in the initial steel and the preparation process are the same as those in Example 1, except that the holding time of the pearlite region in the pearlite spheroidization treatment is different, which is changed to 10h, 12h, 36h and 48h respectively, as follows:

[0115] (1) Steel with a specific composition of Fe-0.4C-5.13Mn (wt%) was melted in a vacuum induction furnace to form a steel ingot with a thickness of 60 mm. The ingot was subjected to a homogenization treatment at 1150°C for 24 hours, then forged to 20 mm after being kept at 1200°C for 1 hour, and the final rolling temperature was 1000°C, followed by air cooling to room temperature. The hot-rolled steel plate was treated as follows:

[0116] (2) Pearlite transformation treatment: Samples were taken from the middle of the hot-rolled plate and austenitized at 850 °C in a tubular furnace filled with industrial argon atmosphere. After holding the temperature for 10 min, the sample was cooled to 550 °C (the furnace cooling rate was 0.17 °C / s), held for 72 h, and air-cooled to room temperature to obtain a steel plate with a layered full pearlite structure.

[0117] (3) Pearlite spheroidization treatment: The steel sheet with a lamellar full pearlite structure was cold rolled with a cold rolling reduction ratio of 70%, and then the sample was kept at 550° C. for 10 h, 12 h, 36 h or 48 h in a tubular furnace filled with industrial argon atmosphere, and then air-cooled to room temperature to obtain a steel sheet with a spheroidized pearlite structure;

[0118] (4) Spheroidized pearlite alienation treatment: The steel plate with spheroidized pearlite structure is placed in a salt bath furnace at 800°C (heating rate of 100°C / s), kept warm for 10s, and air-cooled to room temperature (cooling rate of 10°C / s) to obtain a steel plate with spheroidized ghost pearlite structure;

[0119] (5) Spheroidized ghost pearlite tempering treatment: The steel plate with spheroidized ghost pearlite structure was placed in a 200°C oil bath furnace for 30 min and air-cooled to room temperature to obtain 4 groups of medium carbon and medium manganese high wear-resistant steels.

[0120] The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by the pearlite spheroidization treatment of this embodiment with a holding time of 12h is uniformly distributed spherical retained austenite + tempered martensite, with a spheroidized ghost pearlite structure, a retained austenite volume fraction of 31.2%, an average grain size of 142nm, a hardness of 607.21HV, and a wear resistance of 1.915×10 -5 mm 3 / (N*m). The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by pearlite spheroidization treatment and pearlite zone holding time of 36h in this embodiment is uniformly distributed spherical retained austenite + tempered martensite, with spheroidized ghost pearlite structure, the volume fraction of retained austenite is 28.4%, the average grain size is 137nm, the hardness is 609.17HV, and the wear resistance is 1.907×10 -5 mm 3 / (N*m). The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by pearlite spheroidization treatment with a holding time of 10h is tempered martensite + spherical retained austenite. However, due to insufficient spheroidization time, the retained austenite is unevenly distributed. The volume fraction of retained austenite is 20.6%, the average grain size is 150nm, the hardness is 586.34HV, and the wear resistance is 2.284×10 -5 mm3 / (N·m). The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by pearlite spheroidization treatment with a holding time of 48h is tempered martensite + spherical retained austenite. However, due to the long spheroidization treatment time, some of the retained austenite grains grow. The volume fraction of retained austenite is 23.8%, the average grain size is 155nm, the hardness is 580.45HV, and the wear resistance is 2.126×10 -5 mm3 / (N·m).

[0121] Example 12

[0122] The composition of each element in the initial steel and the preparation process are the same as in Example 1, except that the holding temperatures of the austenite region in the spheroidized pearlite allelation treatment are different, and are changed to 700°C, 730°C, 820°C and 900°C, respectively, as follows:

[0123] (1) Steel with a specific composition of Fe-0.4C-5.13Mn (wt%) was melted in a vacuum induction furnace to form a steel ingot with a thickness of 60 mm. The ingot was subjected to a homogenization treatment at 1150°C for 24 hours, then forged to 20 mm after being kept at 1200°C for 1 hour, and the final rolling temperature was 1000°C, followed by air cooling to room temperature. The hot-rolled steel plate was treated as follows:

[0124] (2) Pearlite transformation treatment: Samples were taken from the middle of the hot-rolled plate and austenitized at 850 °C in a tubular furnace filled with industrial argon atmosphere. After holding the temperature for 10 min, the sample was cooled to 550 °C (the furnace cooling rate was 0.17 °C / s), held for 72 h, and air-cooled to room temperature to obtain a steel plate with a layered full pearlite structure.

[0125] (3) Pearlite spheroidization treatment: The steel plate with a lamellar full pearlite structure was cold rolled with a cold rolling reduction ratio of 70%, and then the sample was kept at 550°C for 24 hours in a tubular furnace filled with industrial argon atmosphere, and air-cooled to room temperature to obtain a steel plate with a spheroidized pearlite structure;

[0126] (4) Spheroidized pearlite alienation treatment: The steel plates with spheroidized pearlite structure were placed in a salt bath furnace at 700°C, 730°C, 820°C or 900°C (heating rate of 100°C / s), kept warm for 10s, and air-cooled to room temperature (cooling rate of 10°C / s) to obtain steel plates with spheroidized ghost pearlite structure;

[0127] (5) Spheroidized ghost pearlite tempering treatment: The steel plate with spheroidized ghost pearlite structure was placed in a 200°C oil bath furnace for 30 min and air-cooled to room temperature to obtain 4 groups of medium carbon and medium manganese high wear-resistant steels.

[0128] The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by the spheroidized pearlite alienation treatment in this embodiment at a temperature of 730°C in the austenite zone is uniformly distributed spherical retained austenite + tempered martensite, with a spheroidized ghost pearlite structure, a retained austenite volume fraction of 26.2%, an average grain size of 131 nm, a hardness of 609.41 HV, and a wear resistance of 1.926×10 -5 mm 3 / (N*m). The microstructure of the medium carbon medium manganese high wear-resistant steel prepared by the spheroidized pearlite alienation treatment in this embodiment at a temperature of 820°C in the austenite zone is uniformly distributed spherical retained austenite + tempered martensite, with a spheroidized ghost pearlite structure, a retained austenite volume fraction of 29.7%, an average grain size of 136nm, a hardness of 602.39HV, and a wear resistance of 1.976×10 -5 mm 3 / (N*m). The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by spheroidizing pearlite with austenite zone holding temperature of 700℃ is tempered martensite + spherical retained austenite. However, due to the low temperature of the alienation treatment, the austenite phase is unstable. The volume fraction of retained austenite is 18.9%, the average grain size is 140nm, the hardness is 578.67HV, and the wear resistance is 2.354×10 -5 mm3 / (N·m). The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by spheroidizing pearlite with austenite zone holding temperature of 900℃ is tempered martensite + spherical retained austenite. However, due to the high temperature of the alienation treatment, the austenite grains are obviously coarse, the volume fraction of retained austenite is 26.2%, the average grain size is 160nm, the hardness is 568.23HV, and the wear resistance is 2.417×10 -5 mm3 / (N·m).

[0129] Example 13

[0130] The composition of each element in the initial steel and the preparation process are the same as those in Example 1, except that the holding time in the austenite zone of the spheroidized pearlite is different, and is changed to 5s, 30s, 120s, and 180s, respectively, as follows:

[0131] (1) Steel with a specific composition of Fe-0.4C-5.13Mn (wt%) was melted in a vacuum induction furnace to form a steel ingot with a thickness of 60 mm. The ingot was subjected to a homogenization treatment at 1150°C for 24 hours, then forged to 20 mm after being kept at 1200°C for 1 hour, and the final rolling temperature was 1000°C, followed by air cooling to room temperature. The hot-rolled steel plate was treated as follows:

[0132] (2) Pearlite transformation treatment: Samples were taken from the middle of the hot-rolled plate and austenitized at 850 °C in a tubular furnace filled with industrial argon atmosphere. After holding the temperature for 10 min, the sample was cooled to 550 °C (the furnace cooling rate was 0.17 °C / s), held for 72 h, and air-cooled to room temperature to obtain a steel plate with a layered full pearlite structure.

[0133] (3) Pearlite spheroidization treatment: The steel plate with a lamellar full pearlite structure was cold rolled with a cold rolling reduction ratio of 70%, and then the sample was kept at 550°C for 24 hours in a tubular furnace filled with industrial argon atmosphere, and air-cooled to room temperature to obtain a steel plate with a spheroidized pearlite structure;

[0134] (4) Spheroidized pearlite alienation treatment: The steel plate with spheroidized pearlite structure is placed in a salt bath furnace at 800°C (heating rate of 100°C / s), kept warm for 30s, and air-cooled to room temperature (cooling rate of 10°C / s) to obtain a steel plate with spheroidized ghost pearlite structure;

[0135] (5) Spheroidized ghost pearlite tempering treatment: The steel plate with spheroidized ghost pearlite structure was placed in a 200°C oil bath furnace for 30 min and air-cooled to room temperature to obtain 4 groups of medium carbon and medium manganese high wear-resistant steels.

[0136] The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by the spheroidized pearlite alienation treatment and the austenite zone holding time of 30s in this embodiment is uniformly distributed spherical retained austenite + tempered martensite, with spheroidized ghost pearlite structure, the volume fraction of retained austenite is 36.7%, the average grain size is 139m, the hardness is 619.27HV, and the wear resistance is 1.739×10 -5 mm 3 / (N*m). The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by the spheroidized pearlite alienation treatment and the austenite zone holding time of 120s in this embodiment is uniformly distributed spherical retained austenite + tempered martensite, with spheroidized ghost pearlite structure, the volume fraction of retained austenite is 26.3%, the average grain size is 129m, the hardness is 613.26HV, and the wear resistance is 1.831×10 -5 mm 3 / (N*m). The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by spheroidizing pearlite with a holding time of 5s in the austenite zone is tempered martensite + spherical retained austenite. However, due to the short treatment time of spheroidizing pearlite, part of the austenite is not completely globalized. The volume fraction of retained austenite is 22.5%, the average grain size is 145nm, the hardness is 585.67HV, and the wear resistance is 2.351×10 -5 mm3 / (N·m). The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by spheroidizing pearlite with a holding time of 180s in the austenite zone is tempered martensite + spherical retained austenite. However, due to the long time of spheroidizing pearlite, the austenite grains are coarse, the volume fraction of retained austenite is 24.1%, the average grain size is 153nm, the hardness is 563.89HV, and the wear resistance is 2.514×10 -5 mm3 / (N·m).

[0137] Embodiment 14

[0138] The composition of each element in the initial steel and the preparation process are the same as in Example 1, except that the heating rates from room temperature to austenite region during the spheroidized pearlite allelation treatment are different, and are changed to 50°C / s and 120°C / s, respectively, as follows:

[0139] (1) Steel with a specific composition of Fe-0.4C-5.13Mn (wt%) was melted in a vacuum induction furnace to form a steel ingot with a thickness of 60 mm. The ingot was subjected to a homogenization treatment at 1150°C for 24 hours, then forged to 20 mm after being kept at 1200°C for 1 hour, and the final rolling temperature was 1000°C, followed by air cooling to room temperature. The hot-rolled steel plate was treated as follows:

[0140] (2) Pearlite transformation treatment: Samples were taken from the middle of the hot-rolled plate and austenitized at 850 °C in a tubular furnace filled with industrial argon atmosphere. After holding the temperature for 10 min, the sample was cooled to 550 °C (the furnace cooling rate was 0.17 °C / s), held for 72 h, and air-cooled to room temperature to obtain a steel plate with a layered full pearlite structure.

[0141] (3) Pearlite spheroidization treatment: The steel plate with a lamellar full pearlite structure was cold rolled with a cold rolling reduction ratio of 70%, and then the sample was kept at 550°C for 24 hours in a tubular furnace filled with industrial argon atmosphere, and air-cooled to room temperature to obtain a steel plate with a spheroidized pearlite structure;

[0142] (4) Spheroidized pearlite alienation treatment: The steel plate with spheroidized pearlite structure is placed in a salt bath furnace at 800°C (heating rate is 50°C / s or 120°C / s), kept warm for 10s, and air-cooled to room temperature (cooling rate is 10°C / s) to obtain a steel plate with spheroidized ghost pearlite structure;

[0143] (5) Spheroidized ghost pearlite tempering treatment: The steel plate with spheroidized ghost pearlite structure was placed in a 200°C oil bath furnace for 30 min and air-cooled to room temperature to obtain two groups of medium carbon and medium manganese high wear-resistant steels.

[0144] The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by the spheroidized pearlite allotropy treatment in this embodiment at a heating rate of 120°C / s from room temperature to austenite is uniformly distributed spherical retained austenite + tempered martensite, with a spheroidized ghost pearlite structure, a retained austenite volume fraction of 31.6%, an average grain size of 119nm, a hardness of 612.19HV, and a wear resistance of 1.821×10 -5 mm 3 / (N*m). The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by spheroidizing pearlite with a heating rate of 50℃ / s from room temperature to austenite is tempered martensite + spherical retained austenite. However, due to the low heating rate, the austenite grains are unevenly distributed. The volume fraction of retained austenite is 28.9%, the average grain size is 132nm, the hardness is 598.47HV, and the wear resistance is 2.107×10 -5 mm3 / (N·m).

[0145] Embodiment 15

[0146] The composition of each element in the initial steel and the preparation process are the same as those in Example 1, except that the cooling rates from the austenite region to room temperature during the spheroidized pearlite allotropy treatment are different, and are changed to 5°C / s and 20°C / s, respectively, as follows:

[0147] (1) Steel with a specific composition of Fe-0.4C-5.13Mn (wt%) was melted in a vacuum induction furnace to form a steel ingot with a thickness of 60 mm. The ingot was subjected to a homogenization treatment at 1150°C for 24 hours, then forged to 20 mm after being kept at 1200°C for 1 hour, and the final rolling temperature was 1000°C, followed by air cooling to room temperature. The hot-rolled steel plate was treated as follows:

[0148] (2) Pearlite transformation treatment: Samples were taken from the middle of the hot-rolled plate and austenitized at 850 °C in a tubular furnace filled with industrial argon atmosphere. After holding the temperature for 10 min, the sample was cooled to 550 °C (the furnace cooling rate was 0.17 °C / s), held for 72 h, and air-cooled to room temperature to obtain a steel plate with a layered full pearlite structure.

[0149] (3) Pearlite spheroidization treatment: The steel plate with a lamellar full pearlite structure was cold rolled with a cold rolling reduction ratio of 70%, and then the sample was kept at 550°C for 24 hours in a tubular furnace filled with industrial argon atmosphere, and air-cooled to room temperature to obtain a steel plate with a spheroidized pearlite structure;

[0150] (4) Spheroidized pearlite alienation treatment: The steel plate with spheroidized pearlite structure is placed in a salt bath furnace at 800°C (heating rate of 100°C / s), kept warm for 10s, and air-cooled to room temperature (cooling rate of 5°C / s or 20°C / s) to obtain a steel plate with spheroidized ghost pearlite structure;

[0151] (5) Spheroidized ghost pearlite tempering treatment: The steel plate with spheroidized ghost pearlite structure was placed in a 200°C oil bath furnace for 30 min and air-cooled to room temperature to obtain two groups of medium carbon and medium manganese high wear-resistant steels.

[0152] The microstructure of the medium-carbon medium-manganese high wear-resistant steel prepared by the spheroidized pearlite alienation treatment of the austenite zone to room temperature at a cooling rate of 20°C / s is uniformly distributed spherical retained austenite + tempered martensite, with a spheroidized ghost pearlite structure, a retained austenite volume fraction of 23.5%, an average grain size of 126nm, a hardness of 615.32HV, and a wear resistance of 1.816×10 -5 mm 3 / (N*m). The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by cooling the austenite zone from spheroidized pearlite to room temperature at a cooling rate of 5℃ / s is tempered martensite + spherical retained austenite. However, due to the slow cooling rate, the decomposition of austenite is aggravated. The volume fraction of retained austenite is 19.8%, the average grain size is 138nm, the hardness is 580.34HV, and the wear resistance is 2.345×10 -5 mm3 / (N·m).

[0153] Example 16

[0154] The composition of each element in the initial steel and the preparation process are the same as in Example 1, except that the oil bath temperature used in the stabilization treatment of the spheroidized ghost pearlite structure is different, which is changed to 150°C, 220°C, 250°C and 280°C, respectively, as follows:

[0155] (1) Steel with a specific composition of Fe-0.4C-5.13Mn (wt%) was melted in a vacuum induction furnace to form a steel ingot with a thickness of 60 mm. The ingot was subjected to a homogenization treatment at 1150°C for 24 hours, then forged to 20 mm after being kept at 1200°C for 1 hour, and the final rolling temperature was 1000°C, followed by air cooling to room temperature. The hot-rolled steel plate was treated as follows:

[0156] (2) Pearlite transformation treatment: Samples were taken from the middle of the hot-rolled plate and austenitized at 850 °C in a tubular furnace filled with industrial argon atmosphere. After holding the temperature for 10 min, the sample was cooled to 550 °C (the furnace cooling rate was 0.17 °C / s), held for 72 h, and air-cooled to room temperature to obtain a steel plate with a layered full pearlite structure.

[0157] (3) Pearlite spheroidization treatment: The steel plate with a lamellar full pearlite structure was cold rolled with a cold rolling reduction ratio of 70%, and then the sample was kept at 550°C for 24 hours in a tubular furnace filled with industrial argon atmosphere, and air-cooled to room temperature to obtain a steel plate with a spheroidized pearlite structure;

[0158] (4) Spheroidized pearlite alienation treatment: The steel plate with spheroidized pearlite structure is placed in a salt bath furnace at 800°C (heating rate of 100°C / s), kept warm for 10s, and air-cooled to room temperature (cooling rate of 10°C / s) to obtain a steel plate with spheroidized ghost pearlite structure;

[0159] (5) Spheroidized ghost pearlite tempering treatment: The steel plates with spheroidized ghost pearlite structure were placed in an oil bath furnace at 150°C, 220°C, 250°C or 280°C for 30 min, and then air-cooled to room temperature to obtain 4 groups of medium carbon and medium manganese high wear-resistant steels.

[0160] The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by the oil bath temperature of 220°C for the spheroidized ghost pearlite structure stabilization treatment in this embodiment is uniformly distributed spherical retained austenite + tempered martensite, with a spheroidized ghost pearlite structure, a retained austenite volume fraction of 28.7%, an average grain size of 121nm, a hardness of 629.86HV, and a wear resistance of 1.921×10 -5 mm 3 / (N*m). The microstructure of the medium carbon medium manganese high wear-resistant steel prepared by the oil bath temperature of 250°C for the spheroidized ghost pearlite structure stabilization treatment in this embodiment is uniformly distributed spherical retained austenite + tempered martensite, with a spheroidized ghost pearlite structure, a retained austenite volume fraction of 24.7%, an average grain size of 125nm, a hardness of 617.25HV, and a wear resistance of 1.862×10 -5 mm 3 / (N*m). The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by stabilizing the spheroidized ghost pearlite structure with an oil bath temperature of 150°C is tempered martensite + spherical retained austenite. However, due to the low tempering temperature, the tempering effect is insufficient. The volume fraction of retained austenite is 23.4%, the average grain size is 140nm, the hardness is 590.12HV, and the wear resistance is 2.281×10 -5 mm3 / (N·m). The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by the spheroidized ghost pearlite structure stabilization treatment with an oil bath temperature of 280℃ is tempered martensite + spherical retained austenite. However, due to the high oil bath temperature, part of the austenite grains are coarsened, the volume fraction of retained austenite is 33.7%, the average grain size is 135nm, the hardness is 575.46HV, and the wear resistance is 2.378×10 -5 mm3 / (N·m).

[0161] Embodiment 17

[0162] The composition of each element in the initial steel and the preparation process are the same as in Example 1, except that the oil bath time used for the stabilization treatment of the spheroidized ghost pearlite structure is different, which is changed to 12 minutes, 1 hour, 2 hours and 3 hours respectively, as follows:

[0163] (1) Steel with a specific composition of Fe-0.4C-5.13Mn (wt%) was melted in a vacuum induction furnace to form a steel ingot with a thickness of 60 mm. The ingot was subjected to a homogenization treatment at 1150°C for 24 hours, then forged to 20 mm after being kept at 1200°C for 1 hour, and the final rolling temperature was 1000°C, followed by air cooling to room temperature. The hot-rolled steel plate was treated as follows:

[0164] (2) Pearlite transformation treatment: Samples were taken from the middle of the hot-rolled plate and austenitized at 850 °C in a tubular furnace filled with industrial argon atmosphere. After holding the temperature for 10 min, the sample was cooled to 550 °C (the furnace cooling rate was 0.17 °C / s), held for 72 h, and air-cooled to room temperature to obtain a steel plate with a layered full pearlite structure.

[0165] (3) Pearlite spheroidization treatment: The steel plate with a lamellar full pearlite structure was cold rolled with a cold rolling reduction ratio of 70%, and then the sample was kept at 550°C for 24 hours in a tubular furnace filled with industrial argon atmosphere, and air-cooled to room temperature to obtain a steel plate with a spheroidized pearlite structure;

[0166] (4) Spheroidized pearlite alienation treatment: The steel plate with spheroidized pearlite structure is placed in a salt bath furnace at 800°C (heating rate of 100°C / s), kept warm for 10s, and air-cooled to room temperature (cooling rate of 10°C / s) to obtain a steel plate with spheroidized ghost pearlite structure;

[0167] (5) Spheroidized ghost pearlite tempering treatment: The steel plate with spheroidized ghost pearlite structure is placed in a 200°C oil bath furnace for 12 min, 1 h, 2 h or 3 h, respectively, and then air-cooled to room temperature to obtain 4 groups of medium carbon and medium manganese high wear-resistant steel.

[0168] The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by the spheroidized ghost pearlite structure stabilization treatment in this embodiment with an oil bath time of 1h is uniformly distributed spherical retained austenite + tempered martensite, with a spheroidized ghost pearlite structure, a retained austenite volume fraction of 26.3%, an average grain size of 136nm, a hardness of 628.13HV, and a wear resistance of 1.723×10 -5 mm 3 / (N*m). The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared with an oil bath time of 2h is uniformly distributed spherical retained austenite + tempered martensite, with a spheroidized ghost pearlite structure, a retained austenite volume fraction of 25.3%, an average grain size of 132nm, a hardness of 621.23HV, and a wear resistance of 1.815×10 -5 mm 3 / (N*m). The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by the spheroidized ghost pearlite structure stabilization treatment with an oil bath time of 12 min is tempered martensite + spherical retained austenite. However, due to insufficient oil bath time, the tempering effect is incomplete. The volume fraction of retained austenite is 24.8%, the average grain size is 142nm, the hardness is 595.12HV, and the wear resistance is 2.310×10 -5 mm3 / (N·m). The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by the spheroidized ghost pearlite structure stabilization treatment with an oil bath time of 3h is tempered martensite + spherical retained austenite. However, due to the long oil bath time, the volume fraction of retained austenite is 23.9%, the average grain size is 161nm, the hardness is 567.18HV, and the wear resistance is 2.387×10 -5 mm3 / (N·m).

[0169] Embodiment 18

[0170] The composition of each element in the initial steel and the preparation process are the same as in Example 1, except that the stabilization treatment of the spheroidized ghost pearlite structure adopts a salt bath, and the salt bath temperature is set to 250° C., and the holding time is set to 12 min, 30 min, 1 h and 3 h, respectively, as follows:

[0171] (1) Steel with a specific composition of Fe-0.4C-5.13Mn (wt%) was melted in a vacuum induction furnace to form a steel ingot with a thickness of 60 mm. The ingot was subjected to a homogenization treatment at 1150°C for 24 hours, then forged to 20 mm after being kept at 1200°C for 1 hour, and the final rolling temperature was 1000°C, followed by air cooling to room temperature. The hot-rolled steel plate was treated as follows:

[0172] (2) Pearlite transformation treatment: Samples were taken from the middle of the hot-rolled plate and austenitized at 850 °C in a tubular furnace filled with industrial argon atmosphere. After holding the temperature for 10 min, the sample was cooled to 550 °C (the furnace cooling rate was 0.17 °C / s), held for 72 h, and air-cooled to room temperature to obtain a steel plate with a layered full pearlite structure.

[0173] (3) Pearlite spheroidization treatment: The steel plate with a lamellar full pearlite structure was cold rolled with a cold rolling reduction ratio of 70%, and then the sample was kept at 550°C for 24 hours in a tubular furnace filled with industrial argon atmosphere, and air-cooled to room temperature to obtain a steel plate with a spheroidized pearlite structure;

[0174] (4) Spheroidized pearlite alienation treatment: The steel plate with spheroidized pearlite structure is placed in a salt bath furnace at 800°C (heating rate of 100°C / s), kept warm for 10s, and air-cooled to room temperature (cooling rate of 10°C / s) to obtain a steel plate with spheroidized ghost pearlite structure;

[0175] (5) Spheroidized ghost pearlite tempering treatment: The steel plates with spheroidized ghost pearlite structure were placed in a 250°C salt bath furnace for 12 min, 30 min, 1 h or 3 h, respectively, and then air-cooled to room temperature to obtain 4 groups of medium carbon and medium manganese high wear-resistant steels.

[0176] The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by 250°C salt bath insulation for 30 min in this embodiment is uniformly distributed spherical retained austenite + tempered martensite, with spheroidized ghost pearlite structure, the volume fraction of retained austenite is 28.1%, the average grain size is 126nm, the hardness is 618.37HV, and the wear resistance is 1.712×10 -5 mm 3 / (N*m). The microstructure of the carbon medium manganese high wear-resistant steel prepared by 250℃ salt bath insulation for 1h is uniformly distributed spherical retained austenite + tempered martensite, with spheroidized ghost pearlite structure, the volume fraction of retained austenite is 27.6%, the average grain size is 132nm, the hardness is 619.52HV, and the wear resistance is 1.728×10 -5 mm 3 / (N*m). The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by 250℃ salt bath insulation for 12min is tempered martensite + spherical retained austenite. However, due to the short salt bath insulation time and insufficient tempering, the volume fraction of retained austenite is 25.7%, the average grain size is 138nm, the hardness is 598.34HV, and the wear resistance is 2.245×10 -5 mm3 / (N·m). The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by 250℃ salt bath insulation for 3h is tempered martensite + spherical retained austenite. However, due to the long salt bath insulation time, some grains grow, the volume fraction of retained austenite is 21.2%, the average grain size is 163nm, the hardness is 572.57HV, and the wear resistance is 2.684×10 -5 mm3 / (N·m).

[0177] Embodiment 19

[0178] The composition of each element in the initial steel and the preparation process are the same as those in Example 19, except that a salt bath is used for stabilization of the spheroidized ghost pearlite structure, and the temperatures of the salt baths are set to 150°C, 280°C, 400°C and 450°C, respectively, and kept warm for 30 minutes, as follows:

[0179] (1) Steel with a specific composition of Fe-0.4C-5.13Mn (wt%) was melted in a vacuum induction furnace to form a steel ingot with a thickness of 60 mm. The ingot was subjected to a homogenization treatment at 1150°C for 24 hours, then forged to 20 mm after being kept at 1200°C for 1 hour, and the final rolling temperature was 1000°C, followed by air cooling to room temperature. The hot-rolled steel plate was treated as follows:

[0180] (2) Pearlite transformation treatment: Samples were taken from the middle of the hot-rolled plate and austenitized at 850 °C in a tubular furnace filled with industrial argon atmosphere. After holding the temperature for 10 min, the sample was cooled to 550 °C (the furnace cooling rate was 0.17 °C / s), held for 72 h, and air-cooled to room temperature to obtain a steel plate with a layered full pearlite structure.

[0181] (3) Pearlite spheroidization treatment: The steel plate with a lamellar full pearlite structure was cold rolled with a cold rolling reduction ratio of 70%, and then the sample was kept at 550°C for 24 hours in a tubular furnace filled with industrial argon atmosphere, and air-cooled to room temperature to obtain a steel plate with a spheroidized pearlite structure;

[0182] (4) Spheroidized pearlite alienation treatment: The steel plate with spheroidized pearlite structure is placed in a salt bath furnace at 800°C (heating rate of 100°C / s), kept warm for 10s, and air-cooled to room temperature (cooling rate of 10°C / s) to obtain a steel plate with spheroidized ghost pearlite structure;

[0183] (5) Spheroidized ghost pearlite tempering treatment: The steel plates with spheroidized ghost pearlite structure were placed in a salt bath furnace at 150°C, 280°C, 400°C or 450°C for 30 min, and then air-cooled to room temperature to obtain 4 groups of medium carbon and medium manganese high wear-resistant steels.

[0184] The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by 280°C salt bath insulation for 30 min in this embodiment is uniformly distributed spherical retained austenite + tempered martensite, with spheroidized ghost pearlite structure, the volume fraction of retained austenite is 25.3%, the average grain size is 126nm, the hardness is 613.28HV, and the wear resistance is 1.768×10 -5 mm 3 / (N*m). The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by 400℃ salt bath insulation for 30min is uniformly distributed spherical retained austenite + tempered martensite, with spheroidized ghost pearlite structure, the volume fraction of retained austenite is 23.2%, the average grain size is 138nm, the hardness is 607.28HV, and the wear resistance is 1.972×10 -5 mm 3 / (N*m). The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by 150℃ salt bath insulation for 30min is tempered martensite + spherical retained austenite. However, due to the low salt bath temperature, the tempering effect is limited. The volume fraction of retained austenite is 21.4%, the average grain size is 140nm, the hardness is 588.63HV, and the wear resistance is 2.301×10 -5 mm3 / (N·m). The microstructure of the medium carbon and medium manganese high wear-resistant steel prepared by 450℃ salt bath insulation for 30min is tempered martensite + spherical retained austenite. However, due to the high salt bath temperature, the austenite grains are coarsened. The volume fraction of retained austenite is 35.1%, the average grain size is 155nm, the hardness is 570.89HV, and the wear resistance is 2.425×10 -5 mm3 / (N·m).

Claims

1. A medium carbon medium manganese high wear-resistant steel with spheroidized ghost pearlite structure, characterized in that: The invention comprises the following chemical elements in percentage by mass: C: 0.3-0.5%, Mn: 4-7%, and the balance is Fe and other inevitable impurities; the matrix is ​​martensite, and residual austenite is dispersed in the martensite matrix, and the volume fraction of the residual austenite is 20-45%.

2. The medium carbon medium manganese high wear-resistant steel with spheroidized ghost pearlite structure according to claim 1, characterized in that: The grain size of the medium carbon, medium manganese and high wear-resistant steel is less than 150nm.

3. The medium carbon medium manganese high wear-resistant steel with spheroidized ghost pearlite structure according to claim 1, characterized in that: The hardness of the medium carbon and medium manganese high wear-resistant steel is greater than 600 HV, and the wear rate is less than 2×10 -5 mm 3 / (N*m).

4. The method for preparing the medium carbon medium manganese high wear resistant steel having spheroidized ghost pearlite structure according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) Lamellar full pearlite formation: The hot-rolled steel sheet of medium carbon and medium manganese steel is heated to the austenite region, heat-insulated, furnace-cooled to the pearlite region, heat-insulated, and air-cooled to obtain a steel sheet with a lamellar full pearlite structure; (2) pearlite spheroidization: cold rolling the steel plate having a layered full pearlite structure obtained in step (1), then heating the cold rolled steel plate to a pearlite region, and heat-insulating the steel plate to achieve pearlite spheroidization, thereby obtaining a steel plate having a spheroidized pearlite structure; (3) pearlite alienation: the steel plate having a spheroidized pearlite structure obtained in step (2) is rapidly heated from room temperature to an austenite region, subjected to heat preservation treatment, and rapidly cooled from the austenite region to room temperature to obtain a steel plate having a spheroidized ghost pearlite structure; (4) Spheroidized ghost pearlite structure stabilization treatment: The steel plate having the spheroidized ghost pearlite structure obtained in step (3) is subjected to low temperature tempering treatment.

5. The method for preparing the medium carbon medium manganese high wear-resistant steel with spheroidized ghost pearlite structure according to claim 4, characterized in that: In step (1), the temperature of the austenite zone is 720-900°C, the heat preservation treatment is 10-60 minutes, and the rate of furnace cooling is less than 1°C / s.

6. The method for preparing the medium carbon medium manganese high wear resistant steel with spheroidized ghost pearlite structure according to claim 4, characterized in that: In step (1), the holding temperature of the pearlite region is 500-600° C., and the holding treatment is performed for 24-96 hours.

7. The method for preparing the medium carbon medium manganese high wear resistant steel with spheroidized ghost pearlite structure according to claim 4, characterized in that: In step (2), the cold rolling reduction ratio is greater than 70%, the pearlite region holding temperature is 500-600° C., and the holding treatment is performed for 12-36 hours.

8. The method for preparing the medium carbon medium manganese high wear resistant steel with spheroidized ghost pearlite structure according to claim 4, characterized in that: In step (3), the holding temperature of the austenite zone is 730-820° C., and the holding treatment is performed for 10-120 seconds.

9. The method for preparing the medium carbon medium manganese high wear resistant steel with spheroidized ghost pearlite structure according to claim 4, characterized in that: In step (3), the heating rate is above 100°C / s, and the cooling rate is above 10°C / s.

10. The method for preparing the medium carbon medium manganese high wear resistant steel with spheroidized ghost pearlite structure according to claim 4, characterized in that: In step (4), the steel plate having the spheroidized ghost pearlite structure is placed in an oil bath furnace at a tempering temperature of 200 to 250° C. for a holding time of 0.5 to 2 h for tempering, or is placed in a salt bath furnace at 250 to 400° C. for a holding time of 0.5 to 1 h for tempering.